FAKTOR-FAKTOR YANG MEMENGARUHI PENYESUAIAN ANALISIS STANDAR BELANJA (ASB) PADA PEMERINTAH DAERAH - PRASETYO, Wahyu Eko; Haryanto (Accounting Global Journal, 2026)
Almost all regions have adjusted the ASB document, but it has not yet been fully used as a basis for preparing the Regional Budget (APBD). This study aims to examine the influence of rational aspects, system improvements, changes in budget behavior, and the dominance of technocratic logic on the implementation variables of ASB adjustments. The methodology uses a mixed approach, with quantitative results as an instrument for criticizing the phenomena that occur. A field study in local governments in Central Java, 101 respondents representing positions were selected by purposive sampling based on the criteria of having been involved in the preparation of ASB. The analysis tool used was SmartPLS 4. The results showed that all independent variables, partially and simultaneously, had a significant positive effect on the dependent variable. This finding proves the continued validity of New Institutional Theory, especially the concept of isomorphism in the ASB adjustment process. However, this study also shows a decoupling phenomenon, where administrative compliance is not directly proportional to its substantial use in regional budgeting. These results imply the need for policy reorientation from merely fulfilling legitimacy to strengthening the integrity of real budgeting data.